Future proofing heritage: Futures Thinking approaches to aid recovery and renewal during the Covid-19 crisis (Libellarium: journal for research in the field of information and related sciences, 2022)
Purpose. This paper aims to illustrate how organisations, especially cultural heritage organisations, can respond to a crisis and plan for recovery when dealing with multiple future uncertainties by applying Futures Thinking techniques. It does this by describing the approach that Historic Environment Scotland (HES) has been taking to plan for recovery and renewal during the COVID-19 pandemic.Approach/methodology/design. The paper uses the case study methodology to explore how different Futures Thinking techniques have been used to build flexibility in HES’s work when facing an uncertain future. The paper will also examine how the methodology used in this process will aid the development of a Futures Thinking toolkit and a Virtual Intelligence Hub in support of all HES’s operations.Findings. This paper demonstrates how Futures Thinking techniques, such as scenario planning, can be effectively used to map critical uncertainties and identify business priorities across different possible scenarios for cultural organisations. It does so by illustrating the journey taken so far by HES to embed Futures Thinking techniques in the organisation, how it engaged with these and used them to begin the process of creating resilience and sustainability in its operations during this crisis.Originality/value. Because cultural organisations do not traditionally engage in Futures Thinking, this paper makes the case that such tools are a valuable approach to foreseeing and surviving crises.
Keywords: COVID-19; crisis response; Futures Thinking; heritage; policy; recovery; strategy